Acquired Hemophilia A Associated with NSAID: A Case Report - Diane Lukito Setiawan; Yetti Hernaningsih (Interna Publishing, 2019)
Acquired hemophilia A (AHA) is a blood clotting disorder caused by the presence of autoantibodies (inhibitors) against factor VIII. The typical symptom of this disorder is bleeding under the skin and soft tissue (rarely in the joints), with no family or personal previous history of bleeding. This case reports is tended to build up awareness for better diagnosis and therapy. Woman, 39 years old, bruises on both forearms are intermittent for 2 months with a history of long term drug consumption for headache treatment. Hemostatic test showed the elongation of activated partial thromboplastin test (APTT) to 87.1 (normal 24.4-44.4 seconds) and the decreament of factor VIII (FVIII) activity to 5% (normal 60-150%). Provision of recombinant factor VIII lowered factor VIII activity to 2%. Factor VIII inhibitor titer was 21.12 BU and diagnosis AHA was made. Inhibitor eradication by methylprednisolone tablet 3x16mg which was given for 2 months, improved the APPT to 46.7 seconds and factor VIII activity to 36%. Acquired Hemophilia A should be suspected in an adult bleeding patient with history of taking a long time non-steroidal anti-inflammatory drugs (NSAIDs). This case is a rare case in Indonesia and therefore the procedure for diagnosis needs to be improved in order to avoid errors in delivering a therapy which can cause the decreament of factor VIII activity.